Hollywood: Old trend in a new form - Bajić, Predrag; Vukašinović, Branko; Zavargo, Iris; Simić, Predrag; Čanadanović, Zorica (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2014)
This paper analyses the way vampires are presented in the modern Hollywood cinematography, as well as the way vampire phenomenon has been changing in the last three and a half decades. The modern vampire is far away from the one from the times of Bela Lugoši. His interpretation of Count Dracula remained one of the most impressive up to now. Once upon a time vampires were recognizable as beings with well-known strong and weak points, with clearly predictable behavior scheme. Considered from the traditional perspective, nowadays vampires stopped being vampires in the modern Hollywood cinematography. The new generations have totally different perception of the vampire image. This paper analyses the time and geographical background in the films, the vampires surroundings, his personal characteristics (appearances, attitude, speech, outfit, behavior), as well as his relation with the victims and the way he dies. Changes were noticed in the 80s of the 20th century. It can be stated that the film “Interview with the Vampire” from 1994 changed for good the traditional conception of the vampire phenomenon and encountered a different one ruining the numerous stereotypes of advantages, disadvantages and habits of the vampire. The new generations of vampires have been presented in films such as “Blade”, “Underworld” and “Twilight”. Vampires are no more presented like malicious and mean beings. Today, they live in cities together with people. Nowadays, there are good and bad vampires, heroes and heroines or vampires with different skin colour. They might live in clans or homosexual communities, they can be comic and seductive, positive or negative. They can survive without human blood, they aren’t affraid of the sunlight or the crucifix, garlic and they do not have to sleep in coffins. Key words: vampire, Dracula, Bram Stoker, Hollywood movie, Transylvania, supernatural creatures, Blade, Van Helsing